MARKETING STRATEGY ANALYSIS IN INCREASING THE NUMBER OF NON-WAGE RECIPIENT PARTICIPANTS AT BPJS KETENAGAKERJAAN BELU-ATAMBUA BRANCH - Seran, Januaria Delviana; Afoan, Felisisima; Manek, Aquidowaris; Naihati, Elfrida Desiderata; Kiha, Emilia Khristina (Yayasan Pendidikan Cahaya Budaya Indonesia, 2025)
Analysis of Marketing Strategies in Increasing the Number of Non-Wage Recipient Membership: A Case Study on BPJS Ketenagakerjaan Belu-Atambua Branch. This study aims to find out: Analysis of Marketing Strategies in Increasing the Number of Non-Wage Recipient Participants at BPJS Employment Belu-Atambua Branch. The data used in this study is primary data obtained through a questionnaire given to 12 respondents. Instrument testing includes validity tests and reliability tests. The object of this research uses observation, interview and questionnaire methods. Meanwhile, the analysis technique uses the SWOT analysis technique using the IFAS matrix method and the EFAS matrix. The results of the IFAS table analysis on the strength factor are: 2.16 and on the weakness factor (Weaknesses) is 1.56 so that the difference between the strength factor and the weakness factor is +0.60. The results of the analysis of the EFAS table on the Opportunity factor (Opportunities) are: 2.06 and on the Threat factor (Threath) is: 1.82 so that the difference between the opportunity factor and the threat factor is +0.70. Based on the results of the analysis of the IFAS matrix and the EFAS matrix, the value of the WS axis on the SWOT diagram is + 0.60 and the value of the OT axis on the SWOT diagram is + 0.24 so that the position of the BPJS Ketenagakerjaan Belu-Atambua Branch office is in Quadrant I (+,+) using the WO Strategy (Weaknesses - Opportunities) then the strategy recommendation at the BPJS Employment Belu- Atambua Branch office is Progressive, meaning that the organization are in prima and steady condition so it is perfectly pssible to continue.